Comics as a Medium for Parent Health Education: Improving Understanding of Normal 9-Month-Old Developmental Milestones - Rosas-Blum, Eduardo D.; Granados, Hector M.; Mills, Brandy W.; Leiner, Marie (Frontiers in Pediatrics, 2018)
Multimodal literacy, a product of modern technology, can aid in the recall of simple-to-complex information for both children and adults. Health education information presented using educational comics takes advantage of multimodal formats and designs based on theoretical models of learning. In this study, we utilized a quasi-experimental design with both pre- and post-intervention testing. The parents of every other patient that attended the well-child appointments of their child aged less than 9 months were invited to participate in this study. Parents significantly increased their recall of information of developmental milestones when the pre- and post-intervention test results were compared, with a significance of p <0.001 at a 95% confidence level. Additional uses of the comic reported by parents included calling their pediatrician with doubts about their own child’s appropriate achievement of milestones, and lending the comics to relatives or friends. The educational comic appeared to assist parents in making meaningful connections between the simplified pictures and the developmental milestones of their child. Comics may provide an alternative for parental education using this multimodal format to explain simple-to-complex issues.